Long-term impacts of agricultural greenhouse expansion on albedo, land surface temperature, and vegetation: Evidence from a typical province in China - Fangxin Chen; Cong Ou; Yue Chen; Xiaochuang Yao; Bowen Niu; Zhenbo Du (Environmental and Sustainability Indicators)
The dramatic expansion of agricultural greenhouses (AGs) in China has raised concerns about its environmental impacts. But our knowledge in this area is still limited, especially the temporal and scale impacts of AGs. To fill this gap, we utilized multiple remote sensing data, time-series segmentation algorithm, and the Mann-Kendall test to analyze the spatiotemporal evolution patterns of AGs in Shandong Province, China from 2001 to 2018. We then explored the impact of AGs on albedo, land surface temperature (LST), and Enhanced vegetation index (EVI) from annual and seasonal analysis perspectives. Results indicated that the total area and number of patches of AGs in Shandong initially grew, then declined, and subsequently grew again. Smaller AGs areas showed lower spatial aggregation and survival rates. Additionally, this study found that AGs have a significant impact on the environment. Increased spatial concentration and longer durations of AGs were linked to more significant reductions in albedo and EVI, along with more pronounced increases in LST. In summer and spring, AGs significantly boosted LST, while in autumn and winter, they significantly reduced albedo. AGs play a crucial role in supporting crop growth during autumn and winter. Moreover, the paper proposed several sustainable AGs management strategies to address these challenges. This study provides observational evidence of the environmental impacts of AGs for promoting sustainable agriculture.